2011
DOI: 10.1007/978-3-642-20285-8_3
|View full text |Cite
|
Sign up to set email alerts
|

The Void Galaxy Survey

Abstract: The Void Galaxy Survey (VGS) is a multi-wavelength program to study ∼60 void galaxies. Each has been selected from the deepest interior regions of identified voids in the SDSS redshift survey on the basis of a unique geometric technique, with no a prior selection of intrinsic properties of the void galaxies. The project intends to study in detail the gas content, star formation history and stellar content, as well as kinematics and dynamics of void galaxies and their companions in a broad sample of void enviro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Statistically, it has been found that galaxies embedded in cosmic voids are bluer (Grogin & Geller 1999;Rojas et al 2004), and tend to have later morphological type (Grogin & Geller 1999;Rojas et al 2004). From observations, it seems that these void galaxies also have stellar disks with smaller radii compared to a control sample of late-type galaxies (van de Weygaert et al 2011). Using galaxy samples from SDSS, Rojas et al (2005) compare the equivalent width (Hα, [OII], [NII], Hβ, [OIII]) of galaxies located in voids or walls.…”
Section: Introductionmentioning
confidence: 99%
“…Statistically, it has been found that galaxies embedded in cosmic voids are bluer (Grogin & Geller 1999;Rojas et al 2004), and tend to have later morphological type (Grogin & Geller 1999;Rojas et al 2004). From observations, it seems that these void galaxies also have stellar disks with smaller radii compared to a control sample of late-type galaxies (van de Weygaert et al 2011). Using galaxy samples from SDSS, Rojas et al (2005) compare the equivalent width (Hα, [OII], [NII], Hβ, [OIII]) of galaxies located in voids or walls.…”
Section: Introductionmentioning
confidence: 99%
“…The underdense environment in voids can be used as a laboratory to study the environmental dependence of galaxy evolution (e.g. [25][26][27]) and they are also particularly sensitive to warm dark matter and neutrinos [28][29][30][31]. While most of the matter of the Universe ends up in collapsed objects at late times, voids account for the majority of the late-time volume of the universe.…”
Section: Introductionmentioning
confidence: 99%
“…Another issue of interest is whether we can observe the intricate filigree of substructure in voids, expected as the remaining debris of the merging of voids and filaments in the hierarchical formation process (van de Weygaert & van Kampen 1993;Sheth & van de Weygaert 2004;van de Weygaert & Platen 2011;Aragon-Calvo 2012). Evidence for such substructure, three interacting galaxies embedded in a common HI envelope, has been reported by Beygu et al (2013), who hypothesised it to be an assembly of a filament in a void.…”
Section: Introductionmentioning
confidence: 99%